Permodelan Numerik Cfd Untuk Mengevaluasi Vortex Induced Vibration (Viv) Pada Long Flexible Cylinder Yang Dipasang Helical Rods Bergap Dengan Pitch 17.5d Dan 5d - Maria Margareta Z. B., Rudi Waluyo Prastianto, dan Handayanu (Politeknik Negeri Madura, 2017)
Vortex-induced Vibration (VIV) of a long flexible riser with and without a smaller helical-shaped cylinder control is investigated numerically by computational fluid Dynamic (CFD) coupling model with computational fluid-structure interaction (FSI) method. In this study, a numerical study of three dimensional (3D) turbulent flow around long flexible cylinder in pairs of suppresion devices in the form of helical rods, with direct current used variations Reynold Number (Re) 2400, 3900, 5500, 6200, 6900 dan 7600. Helical Rods installed 60% of the length of the cylinder, with a 6 mm gap thus providing a comparison between the diameter of the cylinder (D) and the gap (?), ? / D = 0.375. Installation of helical rods with pitch 17.5D and 5D on cylinders with gap ratio ? / D = 0.375, very effective to reduce drag and lift force